Mapping cognitive function screening instruments for patients with heart failure: A scoping review - Arseda, Astuti; Pahria, Tuti; Kurniawan, Titis (Belitung Raya Publisher - Belitung Raya Foundation, 2024)
Background: Patients with heart failure (HF) often experience cognitive impairment, which negatively affects their quality of life. An effective screening tool is essential for nurses and healthcare professionals to assess cognitive function as part of HF management. Although many instruments exist, none are specifically designed for patients with HF. Objective: This study aimed to map the instruments for screening cognitive function in patients with HF. Design: A scoping review. Data Sources: Articles published between 2019 and 2023 were searched in PubMed, ScienceDirect, and Google Scholar, with the last search conducted on 27 January 2024. Review Methods: The review followed the scoping review framework by Arksey and O’Malley and adhered to PRISMA guidelines for scoping reviews. Results: Of the 21 articles meeting inclusion criteria, six cognitive function screening instruments were used across various cognitive domains, effectively identifying cognitive impairment in both inpatient and outpatient HF settings. The Montreal Cognitive Assessment (MoCA) was the most frequently used tool, covering a broad range of cognitive domains. MoCA showed high efficacy with a kappa coefficient of 0.82, Cronbach’s alpha reliability of 0.75, sensitivity of 90%, and specificity of 87%. Conclusion: Instruments like MoCA, Mini-Cog, and TICS-m show promise for assessing cognitive function in patients with HF, each with specific strengths and limitations. MoCA is notable for its comprehensive coverage despite being time-consuming and having language barriers. Further research is needed to revalidate and improve the existing instruments. It is crucial for nurses and healthcare professionals to integrate these tools into regular patient management, highlighting the need for continued research in their application.